TEACHING READING DESCRIPTIVE TEXT THROUGH JEOPARDY GAME TO THE EIGHT GRADE STUDENTS OF STATE JUNIOR HIGH SCHOOL 20 OF PALEMBANG - ASTI VETO MORTINI (JAMBI-ENGLISH LANGUAGE TEACHING, 2017)
The main problem in this research was “Is it effective to use Jeopardy Game in teaching reading descriptive text to the eighth grade students of state junior high school 20 of Palembang?’’ Therefore, the main purposes of this research was to find out whether or not teaching reading descriptive through Jeopardy Game to the Eighth Grade students of State High School 20 of Palembang is significantly effective. In doing this research, the researcher used pre experimental method (one group pre-test post-test design). The population was all students of the state grade of State Junior High School 20 of Palembang in the academic year 2012/2013. The data were got through a written test and analyzed by using the t-test formula. Based on the result of the data analyzed, it showed that, there was significantly difference between the students’ score in the pre-test and those in the post-test. The students’ average score in the post-test (70) was higher than the students’ average in the pre-test (53.8), and the result of the matched t-test was 8.53 at the level significance 0.05 in one tail testing with df (34-1)= 33, the value of the critical in the t-table is 1.692. The t-obtained was higher than t-table 1.692. It means that the Alternative hyporesearch (Ha)was accepted and Null Hyporesearch (Ho) was rejected. In other words, teaching reading descriptive text through Jeopardy Game to the eighth grade students of state junior high school 20 of Palembang was significantly effective.